Pheochromocytoma/Paraganglioma: Review of Perioperative Management of Blood Pressure and Update on Genetic Mutations Associated With Pheochromocytoma - Fishbein, Lauren (J Clin Hypertens (Greenwich), 2013)
Pheochromocytomas and paragangliomas are rare tumors with high morbidity rates caused by excessive catecholamine secretion, even though the majority of tumors are benign. The use of perioperative blockade regimens, together with improved surgical techniques, has greatly impacted the perioperative morbidity associated with these tumors. The old dogma of the “tumor of tens” no longer holds true. For example, at least one third of all pheochromocytomas and paragangliomas are hereditary, with mutations in 1 of 10 well‐characterized susceptibility genes, and one quarter of all tumors are malignant. This review focuses on the perioperative management of pheochromocytoma and paragangliomas and the clinical implications of the associated genetic mutations.